Dentoskeletal and aesthetic effects of mandibular protraction appliance (MPA) using Ricketts analysis - Marcelo CHACON; José Fernando Castanha HENRIQUES; Mario VEDOVELLO FILHO; Carolina Carmo de MENEZES; Silvia Amélia Scudeler VEDOVELLO; Giovana Cherubini VENEZIAN; Adriana Simoni LUCATO (Universidade Estadual Paulista, 2018)
Abstract Objective This study was designed to evaluate the skeletal, dental and soft tissue effects of mandibular deficiency treatment with the mandibular protraction appliance (MPA) using 12 factors of the Ricketts analysis. Material and method This cross-sectional retrospective study sample consisted of a group (n = 27), with Class II malocclusion, convex facial profile, increased horizontal trespass and mandibular deficiency, with initial mean age of 12.27 and final of 15.18 years, treated with fixed appliance combined with the MPA, in an average time of 2.9 years. Initial and final radiographs were investigated using Ricketts analysis. The dependent t-test was used to compare the initial and final phases of the MPA group, with a significance level of 5%. Result Statistically significant differences were observed for dental changes such as retrusion (p=0.000) and palatal inclination of the maxillary incisors (p=0.000); protrusion (p=0.000) and buccal inclination of the mandibular incisors (p=0.000); increased interincisal angle (p=0.002) and improved molar ratio (p=0.003). There was also a restriction of the anterior displacement of the maxilla (p=0.000) and a decrease in the mandibular plane angle (p=0.024). The variable inferior labial protrusion with significance (p=0.000), reiterated the improvement in the profile. Conclusion The effects of MPA on correction of malocclusion Class II, verified by Ricketts analysis occurred predominantly by dentoalveolar changes, decrease in the Mandibular Plane Angle, and restriction of anterior displacement of the maxilla, which contributed to the improvement in the patient's profile.